Differences in the Fate of Surface and Subsurface Microplastics: A Case Study in the Central Atlantic - Igor Zhdanov; Svetlana Pakhomova; Anfisa Berezina; Ksenia Silvestrova; Natalia Stepanova; Evgeniy Yakushev (Journal of Marine Science and Engineering, 2023)
Plastic is recognized as a threat to marine ecosystems, and estimating the level of plastic and microplastics (MPs) pollution of the World Ocean is, nowadays, the goal of many studies. However, the use of different methods for the sampling and analysis of MPs leads to the problem of comparing the results obtained. Studies on surface MPs pollution of the surface sea water are based on the application of the manta or neuston nets that collect water from the upper 10–20 cm layer (the “surface” MPs) or submersible pumping systems that collect water from the water layer 3 to 5 m below the sea surface (the “subsurface” MPs). These two techniques allow the collection of particles of different size fractions, i.e., >300 µm for the surface MPs and >100 µm for the subsurface MP. However, it is shown that microplastics found in the surface and subsurface layers differ not only in the size of the items found, but also in morphology, types of polymers, abundance, weight concentration and their spatial distribution. Different hydrodynamic processes affect the fate of the plastic found exactly at the sea surface and several meters deeper. The aim of this work was to study the distribution of surface and subsurface MPs and to reveal an influence of oceanographic conditions on their spatial distribution, using as an example the open ocean waters of the Central Atlantic.